TUGAS DAN KEDUDUKAN LEMBAGA KEJAKSAAN SEBAGAI PELAKSANA KEKUASAAN PENUNTUTAN DALAM SISTEM PEMERINTAHAN PRESIDENSIAL BERDASARKAN UNDANG-UNDANG NOMOR 16 TAHUN 2004 TENTANG KEJAKASAAN REPUBLIK INDONESIA - ANTONIUS, SH. A.2021141100, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2016)
ABSTRACTThis thesis discusses the prosecutor's duties and position the institution as enforcers prosecution in the presidential system of government based on Law Number 16 Year 2004 About the Prosecutors of the Republic of Indonesia. The method used in this research is normative juridical approach. From the results of this thesis can be concluded that the RI Attorney THAT notch as executor Prosecution Authority and the position of the Attorney General Government System In accordance with Article 19 paragraph (20) in conjunction with Article 22 of Law No. 16 of 2004 can be concluded that the Attorney General is not independent. This is due to the attorney general is appointed and dismissed by the President. The position of the prosecutor that the placement of RI as part of the prosecution is that the power of attorney was not set explicitly in the Constitution of 1945. The arrangement is only implied implicit in Article II of the Transitional Provisions of the 1945 Constitution and the 1945 Constitution after the changes in Article 24 paragraph (3). Understanding Attorney and the Attorney General included in the scope of judicial power. Article 24 paragraph (1) of the Act of 1945 states that,